Rapid Yield Gap Assessment: African Development Bank's Priority Commodities - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
Yield gap of nine priority commodities of the African Development Bank was assessed and aggregated at two levels across the Africa continent: 1) agro-ecological zones and 2) agro-ecological zones by country. In this rapid assessment, the yield gap was defined as the percentage difference between the actual yield estimated from spatially-disaggregated crop production statistics database and the potential yield retrieved from the FAO's Global Agro-Ecological Zones database, both at the 10-km pixel level.